Peptídeos sintéticos são uma potencial ferramenta de imunodiagnóstico para a detecção da infecção de Toxoplasma gondii em suínos - Oliveira, Débora Karolla de Freitas (2024)
Toxoplasma gondii, a zoonotic parasite with worldwide distribution, is a major public health concern since it may be transmitted through the consumption of undercooked meat. Surveillance of the disease in pigs is a crucial one health initiative to effectively prevent infection, as well as, minimize economic losses in the meat industry. To date, serological diagnosis continues to pose significant challenges in these settings, especially due to the expensive and laborious antigen preparations. Therefore, this study aims in the development of immunoassays based on synthetic peptides, derived of B cell epitopes predicted from known antigens, in order to detect previous exposure of pigs to T. gondii. For that purpose, we predicted and synthesized 18 peptides from SRS, GRA, MIC, and ROP proteins using bioinformatic tools. We performed peptide-based ELISAs with positive serum samples extracted from pigs experimentally infected with T. gondii tachyzoites or oocysts, alongside with negative uninfected controls. Peptides were able to efficiently distinguish positive and negative samples, however, sequences predicted from SRS29B, MAG1, SRS59B, GRA1, GRA5, and GRA7 showed superior immunoreactivity. Additionally, we also tested the molecules in a dot blot system, in which all peptides presented similar performance. Neither assay, regardless of the peptides used, were able to distinguish T. gondii infective forms. Based on these results, we were able to select several peptides extracted from T. gondii proteins that may be used in serological assays directed to determine the previous exposure of pigs to T. gondii.